Mandatory Human Rights Due Diligence Laws: Blurring the Lines between State Duty to Protect and Corporate Responsibility to Respect? - Krajewski, Markus (Nordic Journal of Human Rights, 2023)
This paper assesses mandatory human rights laws for companies in light of the public-private divide in international human rights law. It asks whether and to what extent these laws contribute to the blurring of the private-public divide by reducing or even eliminating the boundaries between the obligations of public and private entities. The paper also assesses whether maintaining the divide is normatively desirable from the perspective of international human rights law. It first explains the public-private divide in international human rights law by recalling its doctrinal basis, reflecting on attempts to create binding obligations for companies in international human rights law, and assessing the United Nations Guiding Principles on Business and Human Rights within this framework. Next, it analyses existing and proposed domestic laws and legal instruments aimed at establishing human rights obligations for companies. It highlights the difference between approaches directly binding companies to human rights and laws requiring human rights due diligence. Based on this, the paper concludes that the public-private divide remains a useful analytical framework for international human rights law even though the boundaries between public and private are increasingly blurred in practice.
CRIS-Team WoS Importer:2023-05-12